Dietary fat alters the expression of cortistatin and ghrelin systems in the PBMCs of elderly subjects: Putative implications in the postprandial inflammatory response. Issue 9 (28th July 2014) - Gahete, Manuel D.; Luque, Raúl M.; Yubero‐Serrano, Elena M.; Cruz‐Teno, Cristina; Ibañez‐Costa, Alejandro; Delgado‐Lista, Javier; Gracia‐Navarro, Francisco; Perez‐Jimenez, Francisco; Castaño, Justo P.; Lopez‐Miranda, José
<x xml:space="preserve">Abstract</x> Scope Dietary fat influences systemic inflammatory status, which determines the progression of age‐associated diseases. Since somatostatin (SST), cortistatin (CORT), and ghrelin systems modulate inflammatory response, we aim to comprehensively characterize the presence and regulation of the components of these systems in the peripheral blood mononuclear cells (PMBCs), a subset of white blood cells placed at the crossroad between diet and inflammation, in response to diets with different fat composition, and during the postprandial phase in elderly subjects. Methods and results The applied nutrigenomic, inflammation‐related PBMC‐based approach revealed that the majority of components of SST/CORT and ghrelin systems are present in the human PBMCs. Particularly, CORT, SST/CORT receptors (sst2, sst3, sst5, and sst5TMD4), ghrelin, its acylating enzyme (GOAT), In1‐ghrelin variant, and GHSR1b were detected in PBMCs. Their expression was altered in the long‐term by diet composition, and in the short‐term, during the postprandial phase. Of particular relevance is the postprandial elevation of CORT, sst2, and sst5 expression in PBMCs of subjects under n‐3 PUFAs‐enriched diet. Conclusion Our results suggest a potential relevant role of CORT/ssts and ghrelin systems in regulating PBMCs response to nutrient intake, which could help to explain the positive effects of n‐3 PUFAs‐enriched diets in reducing the inflammatory response.